ATP mimics as glutamine synthetase inhibitors : an exploratory synthetic study - Salisu, Sheriff Tomilola (Rhodes University, Faculty of Science, Department of Chemistry, 2008)
Using a mechanism-based approach to drug discovery, efforts have been directed towards developing novel ATP mimics that can act as GS inhibitors. The purine-based systems, adenosine, adenine and allopurinol, were identified as possible scaffolds for potential ATP mimics, while various meta-disubstituted benzenoid compounds, 3-aminobenzonitrile, 3-aminophenol, resorcinol, 3-aminobenzyl alcohol, 3-hydroxybenzoic acid and 3-aminobenzoic acid have been explored as adenine analogues. These compounds were treated with different alkylating and acylating agents. Allylation of all the substrates was achieved using allyl bromide and N-9 alkylation of protected allopurinol was effected using a number of specially prepared Baylis-Hillman adducts. Acylation of the benzenoid precursors with chloroacetyl chloride, acetoxyacetyl chloride, acryloyl chloride and specially prepared 2,3,4,5,6-pentaacetylgluconoyl chloride afforded the corresponding mono- and /or diacylated products in varying yields (4-96%). Elaboration of the alkylated and acylated products has involved the reaction of hydroxy systems with diethyl chloro phosphate and chloro derivatives with triethyl phosphite in Arbuzov-type reactions to afford phosphorylated products. In all cases, products were fully characterized using 1- and 2-D NMR analysis and, where appropriate, high-resolution mass spectrometry. The application of Modgraph and ChemWindow NMR prediction programmes has been explored and the resulting data have been compared with experimental chemical shift assignments to confirm chemical structures and, in some cases, to establish the position of allylation or acylation. Experimental assignments were found to be generally comparable with the Modgraph data, but not always with the ChemWindow values. The docking of selected products in the 'active-site' of GS and their structural homology with ATP, both in their free and bound conformations have been studied using the ACCELERYS CeriusÂ² platform. All the selected ATP mimics exhibit some form of interaction with the 'active-site' residues, and a number of them appear to be promising GS ligands.
Keywords: Glutamine synthetase; Tuberculosis -- Treatment; Tuberculosis -- Chemotherapy; Adenosine triphosphate; Adenosine triphosphate -- Synthesis; Drug development